2011
DOI: 10.1111/j.1463-1326.2010.01344.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with d-chiro-inositol prevents autonomic and somatic neuropathy in STZ-induced diabetic mice

Abstract: DCI has a neuroprotective action in both autonomic and somatic nerves in STZ-induced DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
1
18
0
3
Order By: Relevance
“…The finding that chiro-inositols activate insulin signaling in CNS neurons is in harmony with results established previously in peripheral tissues, which demonstrated increased plasma glucose utilization in rats and rhesus monkeys after chiro-inositol administration (42,62). Insulin mimetic effects are consistent with the ability of DCI to protect against autonomic and somatic neuropathy in diabetic mice (44). Our results extend this protection against neuropathy to CNS neurons in a manner that is germane to Alzheimer's pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that chiro-inositols activate insulin signaling in CNS neurons is in harmony with results established previously in peripheral tissues, which demonstrated increased plasma glucose utilization in rats and rhesus monkeys after chiro-inositol administration (42,62). Insulin mimetic effects are consistent with the ability of DCI to protect against autonomic and somatic neuropathy in diabetic mice (44). Our results extend this protection against neuropathy to CNS neurons in a manner that is germane to Alzheimer's pathogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetic db/db mice, diabetic Rhesus monkeys and T2D patients showed a linear correlation between decreased urinary DCI excretion and the degree of insulin resistance . Previously, it was reported that DCI decreases the level of oxidative stress in endothelial cells, and DCI seems to prevent the inflammatory neuronal damages observed in rats treated with streptozotocin …”
Section: Introductionmentioning
confidence: 90%
“…For induction of diabetes we used a previously described methodology [11]. The mice were subjected to fasting for 6 hours and then anesthetized by thiopental (40mg/kg/2.5% IP) and kept in a prone position for an intraperitoneal (IP) injection of streptozotocin (solution 70mg/kg - STZ) dissolved in citrate buffer solution (pH 4.5).…”
Section: 0 Materials and Methodsmentioning
confidence: 99%